Carl Schmitt: A Theory on Politics and Theology - Lamprou, Eleni (Conatus - Journal of Philosophy, 2017)
Carl Schmitt in his book Political Theology: Four Chapters on the concept of sovereignty deals with the issue of sovereignty and furthermore in which cases the sovereign is likely to emerge. Initially, he tries to define what sovereignty is. He claims that sovereignty has to do with a ‘situation of extraordinary emergency’. In such a case, the sovereign ought to concede the existence of the exception of the current legal status and in the end, he should defend the public security, the order of the state and furthermore he has to aim at the salut public. Schmitt speaks for the suspension of the current order and the existence of a state but not a state of justice. He maintains that there is no anarchy or iniquity since the sovereign has legislated and no law can exist or be implemented in chaos. The law has been sited by the sovereign arbitrarily. Thereafter, a genealogical approximation for the term of sovereignty has been attempted, which has been based on claims of Bodin, Kelsen (whose theory has been counterfeited by Schmitt), Krabbe and Thomas Hobbes. The most important part in his book is the analysis of the term of political theology, the way in which religion interferes with the legal state of law, through one sovereign that creates the law and his decisions are vicious. Science and theology are mixed as a social phenomenon. Schmitt believes that sovereignty must in no way be hidden behind religion but it must be seated in science. He thinks that monarchy has found the power to create a state of law and this has been maintained through religion.